La pauvreté urbaine à Mexico : une approche de la diversité des colonies populaires - Antonine Ribardière; Jean-François Valette (EchoGéo)
In Mexico, urban poverty has been largely addressed through the concept of marginalidad theorized during the popular development of colonias populares, which were the main modality of physical growing of the city since the 1940s. This notion allows us to understand both social and spatial forms of poverty. Today, the link between poverty and popular colony needs to be revisited. From the 2010 population census, we offer an updated picture of the socio-spatial forms of poverty in Mexico City. Then, we examine the specific forms of settlement of colonias populares. The high diversity highlighted refers to paths consolidation and political dimension of the regularization process, typical of this mode of settlement.